Industrialización Azucarera Nova Miel - Alvarado Robalino, Katerin Nataly (2017)
The present study was carried out with the objective of obtaining hydrolysed honey from the sugarcane juice by enzymatic inversion using the enzyme invertase, in addition to evaluating quality, safety and efficiency of processes as new alternatives for the industrialization of sugarcane juice. With the purpose of dynamizing the agroindustrial subsector panelero since it obtained greater yield, in the finished product. The concentration reached was lower than the panela and natural sugar, being a honey concentrated at temperatures above those of boiling, for that reason was packed in hot glass containers. The nutritional and process quality is due to the fact that each stage in the clarification and concentration was controlled. The clarification is important due to the natural clarifying substances action, in this case the mucilages of the Yausabara, which allows to separate the non-sugars dissolved in the juice and thick impurities due to the increase of temperature of the juice and that is realized under the principle of flotation and sedimentation. When a physicochemical analysis (turbidity) was performed to obtain the best treatment, an ADEVA (A x B x C) showed that the best treatment was t5 (-1, -1, 1), with a mucilaginous solution of 50g / 500ml, 3% at the incorporation temperature of 70 ° C. Obtaining honey by enzymatic inversion was given by the incorporation of the enzyme invertase added in different amounts and temperatures after clarifying the juice of the sugar cane. A physicochemical analysis (viscosity, solids solids and presence of crystals) was carried out to obtain the best treatment, by ADEVA (A x B x C), the best was t14 (0, 0, 0) with a concentration of enzyme 7.5 g of enzyme, at an incorporation temperature of 55 ° C and a activation time of 12 hours. The hydrolysed honey obtained was objectively assessed by physicochemical and microbiological analyzes which gave acceptable results since they are with in the parameters allowed by the INEN 1572, 1632 standards and CODEX Alimentarius in force equivalent to those of honey. Finally, the cost of the product was determined in the presentation of a container of 250ml which is 1.74 ctvs., and a PVP of 2.18 ctvs., Cost accessible to the consumer